Nonlinear Elastic Foundation Plate Model Study on Overlying Strata Movement in Working Face with Solid Backfilling Mining - Baifu An; Nailu Li; Qiaomei Yi; Dong Zhang; Hailong Wang (Shock and Vibration)
Although solid backfilling materials are featured with obvious nonlinear stress-strain properties, for a long time, they have been usually simplified as linear elastic materials for approximate calculation in mechanical analysis, so it is difficult to accurately reflect their deformation process. Based on test results of solid backfilling materials’ compaction characteristics, this paper provides a solution method to generate their elastic foundation coefficient. One multiparameter elastic foundation has been used to reflect stress-strain characteristics of solid backfilling material. In addition, the paper establishes a thin plate on a nonlinear elastic foundation model by adopting semianalytical and seminumerical method and obtains the relational expression between roof deflection, roof stress, and backfilling material’s compressive deformation. In combination with geological conditions in a specific mine, the paper probes into what influence both backfilling material’s particle size and the initial compaction force that the backfilling material bears could exert on roof subsidence and stress. Finally, the proposed model has been verified with measured data from industrial tests.